The national database of the German Collaborative Arthritis Centres: II. Treatment of patients with rheumatoid arthritis - Zink, A.; Listing, J.; Niewerth, M.; Zeidler, H.; German Collaborative Arthritis, Centres (Ann Rheum Dis, 2001)
OBJECTIVE: To describe current treatment of patients with rheumatoid arthritis (RA) in German rheumatology. METHODS: Data from the German rheumatological database of 1998, comprising clinical and patient questionnaire data of 12 992 outpatients with RA seen at 24 collaborative arthritis centres in Germany, were analysed. RESULTS: At the time of documentation, 88% of the patients with RA were undergoing disease modifying antirheumatic drug (DMARD) treatment. Methotrexate (MTX) was prescribed to 56% of the patients (61% with seropositive and 45% with seronegative RA). Combination treatment was used in 15%. MTX was the drug of first choice even in patients with up to one year’s disease duration (49%), followed by antimalarial drugs (21%). Patients treated by non-rheumatologists within the previous year had received DMARD treatment in only 33% of the cases. In steroid treatment, low doses (< or = 7.5 mg/day) were used by rheumatologists much more often (44%) than higher doses (12%). 16% of the patients had been inpatients during the previous year, with a median length of stay accumulated over the year of 21 days. Together with stays in inpatient rehabilitation, 22% of all patients had had some form of inpatient treatment. Comprehensive measures such as occupational therapy and patient education were prescribed to fewer than 12% of the patients, mostly during their hospital stay. CONCLUSION: German rheumatologists do follow recent recommendations about early and effective treatment. However, there are still deficits in outpatient care with non-medicinal measures like occupational therapy and patient education, which may partly explain the high hospital admission rates.